DETERMINATION OF RESIDUAL INTERNAL STRESSES OF CYLINDRICAL DETAILS IN THE PROCESS OF THEIR DISTRIBUTION - Іванкова, Олена; Общий, Ярослав; Кисіль, Юрій; Федін, Віталій (SWorldJournal, 2024)
An important task of the technical service is to increase the reliability of agricultural machinery.The improvement of repair production requires the implementation of high-performance processes of restoration of worn machine parts. The method of distrib